Alterations in rat serum proteome and metabolome as putative disease markers in sepsis - Hinkelbein, Jochen; Feldmann, Robert Enrico; Schubert, Charlotte; Peterka, Anna; Schelshorn, Dominik W.; Maurer, Martin H.; Kalenka, Armin (The journal of trauma and acute care surgery, 2009)
Objectives: - Despite a decreased mortality from sepsis, the absolute number of sepsis-related deaths has actually increased during the last years. At present, there are no biological markers available that can reliably assist early clinical diagnosis and the prompt initiation of therapy. This study investigated the changes in serum protein expression in a coecal ligature and puncture model of rat sepsis at 12, 24, and 48 hours after the induction of sepsis using differential proteomics. - Methods: - Sixty-two male Wistar rats were randomly assigned to a sepsis group (coecal ligature and puncture; n = 46) or a sham group (n = 16). Surviving rats were killed 12 hour (n = 6), 24 hour (n = 9), or 48 hour (n = 4) after operation, and their serum lysates were subjected to two-dimensional gel electrophoresis and peptide mass fingerprinting. A systematic functional network mapping and molecular pathway analysis were performed using Ingenuity Pathways Analysis. - Results: - Septic mortality was 58.7%, but no rat of the sham group was lost. Per gel, an average of 1,082 ± 10 spots could be discriminated, of which 40 different protein spots were differentially expressed (p < 0.01). From the total of 40, the number of regulated protein spots was 13 (12 hour group) versus 10 (24 hour group) versus 18 (48 hour group). Ingenuity pathways analysis identified 10 of the differential proteins and allocated them to a pathway of tissue inflammation. - Conclusions: - The present study quantitatively detected several proteins differentially expressed in acute sepsis. Since a longer time-period was investigated and compared with previous studies, the results may offer new insights into septic organ dysfunction and altered protein pathways. The horizontal analysis of protein expression arrays and systematic biochemical pathways may represent an important new tool for the clinical assessment of septic conditions and support the development of early sepsis markers.
Gesehen am 13.01.2025